2017
DOI: 10.1073/pnas.1612907114
|View full text |Cite
|
Sign up to set email alerts
|

Sediment supply controls equilibrium channel geometry in gravel rivers

Abstract: In many gravel-bedded rivers, floods that fill the channel banks create just enough shear stress to move the median-sized gravel particles on the bed surface (D 50 ). Because this observation is common and is supported by theory, the coincidence of bankfull flow and the incipient motion of D 50 has become a commonly used assumption. However, not all natural gravel channels actually conform to this simple relationship; some channels maintain bankfull stresses far in excess of the critical stress required to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 46 publications
4
118
2
Order By: Relevance
“…In addition, for the threshold‐based load relation in Figure c, the gravel‐related channel‐forming discharge is associated with a Shields stress ( τg=0.033) that is only slightly larger than its critical value ( τcg=0.027). This is consistent with findings with respect to the bankfull discharge in gravel‐bed rivers [ Parker , , ; Parker et al , ; Phillips and Jerolmack , ; Pfeiffer et al , ]. The sand‐related channel‐forming discharge in Figure c is associated with a Shields stress ( τs=0.29) that is significantly larger than its critical value ( τcs=0.14), which is consistent with the findings by Parker [, ].…”
Section: The Channel‐forming Versus the Effective Dischargesupporting
confidence: 91%
“…In addition, for the threshold‐based load relation in Figure c, the gravel‐related channel‐forming discharge is associated with a Shields stress ( τg=0.033) that is only slightly larger than its critical value ( τcg=0.027). This is consistent with findings with respect to the bankfull discharge in gravel‐bed rivers [ Parker , , ; Parker et al , ; Phillips and Jerolmack , ; Pfeiffer et al , ]. The sand‐related channel‐forming discharge in Figure c is associated with a Shields stress ( τs=0.29) that is significantly larger than its critical value ( τcs=0.14), which is consistent with the findings by Parker [, ].…”
Section: The Channel‐forming Versus the Effective Dischargesupporting
confidence: 91%
“…It also has been suggested that rivers maintain a roughly constant bankfull Shields number for gravel bed ( τbf= 0.049) and for sand‐bed ( τbf= 1.86) rivers (Parker, ; Parker et al, ). However, recent empirical evidence has shown that the bankfull Shields number is a variable depending on a series of parameters, such as the dimensionless bed material grain size ( D=true(Rgtrue)1/3v2/3 D50 (Van Rijn, ), where ν is the kinematic viscosity of water), channel slope, and sediment supply (Li et al, ; Pfeiffer et al, ; Trampush et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This model is supported by both global compilations of data and case studies of individual rivers that demonstrate that bedload-dominated gravel-bedded rivers are slightly offset from a threshold channel (Phillips and Jerolmack, 2016;Gaurav et al, 2015;Métivier et al, 2016). Several studies have presented evidence that sediment supply and bank vegetation may drive gravel channels further above threshold (Pfeiffer et al, 2017;Millar and Quick, 1998). Values for Shields stress in gravel-bed rivers reported for a wide range of environments, however, rarely exceed 2-3 times critical.…”
Section: Introductionmentioning
confidence: 60%